Tribological properties study of N-containing heterocyclic imidazoline derivatives as lubricant additives in water-glycol. (December 2016) - Xiong, Liping; He, Zhongyi; Han, Sheng; Tang, Jun; Wu, Yinglei; Zeng, Xiangqiong
Abstract: Tribological and anticorrosion behaviors of imidazoline as water soluble additives is one of research hotspot. Two kinds of N-containing heterocyclic (benzotriazole and mercaptobenzothiazole) imidazoline compounds were synthesized and their tribological, antirust and anticorrosion behaviors were investigated. Results showed that they showed good anticorrosion, extreme pressure and antiwear properties. However, mercaptobenzothiazole-containing imidazoline showed excellent tribological property than benzotriazole-containing imidazoline. Their different tribological properties are closely corresponded to the different structure. There exist a synergistic tribological effect of the N-containing heterocyclic species and imidazoline group in additive, and the synergistic effect improves the tribological performances of water-glycol. The boundary tribofilm which contained organic nitrogen compounds, iron oxide, sulfide and so on, was the main factor to improve the tribological performances of water-glycol. Highlights: N-containing heterocyclic imidazoline compounds had been synthesized and used as water-soluble lubricant additive. These additives showed good anticorrosion and tribological performances, and MM express better tribological properties. Mercaptobenthiazole group plays a crucial role, suggesting the importance of S-N synergetic effect.